Zaragoza: Microhistoria y reflexiones de las independencias hispanoamericanas (1814) (ACME, 2021)
The following article is the result of a research work related to microhistory in which social characteristics stand out at the beginning of the 19th century, when a series of political and military events took place that led to the independence of the nascent Hispanic-American republics. Zaragoza is a town that is located in Antioquia, northern Colombia, which at the time was important because of the gold mining boom. It is in this scenario that a judicial situation was carried out with unusual details, definitive to understand the dimension of historical processes throughout Latin America.